Determination of bacterial and viral pathogen spectra and identification of multi drugs resistance gene CTX-M1 in Klebsiella pneumoniae isolated from acute respiratory infections children aged under-5 from two hospital settings of Dhaka city - Hossain, Mohammad Amir (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.